ANALISIS PERSEPSI MAHASISWA PENDIDIKAN EKONOMI TERHADAP MEDIA PEMBELAJARAN QR CODE PADA MICROTEACHING - Hutabarat, Apriani; Siska Lumbanbatu; Yulce Karubuy; Suriyani Br Ginting; Deni Adriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology has encouraged the adoption of innovative learning media in higher education, particularly in Micro Teaching courses. However, many students have not yet optimally utilized technology-based learning media. This study aims to examine the perceptions of Economic Education students regarding the use of QR Code-based learning media in Micro Teaching. A quantitative descriptive approach was employed in this research. Data were collected through a questionnaire distributed to 41 students who had completed the Micro Teaching course. The findings revealed that the overall average score of student perceptions was 3.23, which falls into the positive category. The highest score was observed in the aspect of teaching effectiveness, while the lowest was found in the quality of learning materials. It can be concluded that the use of QR Code-based learning media has a positive impact on the Micro Teaching learning process, although improvements in the quality of learning materials are still necessary